2017
DOI: 10.1080/21691401.2017.1284858
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of albumin-derived perfluorocarbon-based artificial oxygen carriers in the Langendorff-heart

Abstract: The aim of this study was to prove whether albumin-derived perfluorocarbon-based nanoparticles (capsules) can operate as a novel artificial oxygen carrier in a rat Langendorff-heart perfusion model. Hearts perfused with capsules showed increased left ventricular pressure and rate pressure product compared to hearts perfused with pure Krebs-Henseleit (KH)-buffer. The capsules prevented the myocardium from functional fail when in their absence a noxious ischemia was observed. Capsules did not change rheological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(73 citation statements)
references
References 41 publications
(46 reference statements)
0
64
0
9
Order By: Relevance
“…In vitro experiments, perfusion of isolated Langendorff hearts as well as in vivo toxicities studies showed promising results for the applicability of albumin-derived perfluorocarbon-based capsules as blood substitutes and dispelled concerns on capsule aggregation in vivo 13,15 . Still, physiological in vivo "proof of concept" was missing.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments, perfusion of isolated Langendorff hearts as well as in vivo toxicities studies showed promising results for the applicability of albumin-derived perfluorocarbon-based capsules as blood substitutes and dispelled concerns on capsule aggregation in vivo 13,15 . Still, physiological in vivo "proof of concept" was missing.…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of O 2 into the PFC droplet happens faster than the uptake of O 2 into the RBCs. This is unimpeded by the emulsifier [ 54 , 106 ]. Furthermore, PFOCs stay rather close to the endothelia and shorten the diffusion distance between RBCs and the endothelium whilst acting as stepping-stones for O 2 (Fig.…”
Section: Pfc-based Oxygen Carriers: Peculiarities and Fields Of Applimentioning
confidence: 99%
“…This technique needs O 2 carriers to maintain the physiological status or to regenerate the tissue. Some new attempts show promising results in the ex vivo perfusion of different organs with PFOCs in low doses oxygenated with carbogen or pure O 2 , respectively [ 76 , 98 , 106 ]. The above-mentioned universal gas dissolubility opens another path off the beaten tracks for PFOCs.…”
Section: Pfc-based Oxygen Carriers: Peculiarities and Fields Of Applimentioning
confidence: 99%
“…Albumin-derived perfluorodecalin-filled nanocapsules showed promising results in a first in vivo toxicity study (Wrobeln et al, 2017a) and protected a Langendorff heart (rat) during massive ischemia (Wrobeln et al, 2017b). Similarly, a novel PFC emulsion increased myocardial O 2 delivery, improved cardiac function, and generated a more physiologic redox state in a Langendorff heart (rabbit) compared with perfusion without the PFC emulsion (Kuzmiak-Glancy et al, 2018).…”
Section: In the Pipeline/preclinical Developmentmentioning
confidence: 99%